Adaptive ERK signalling activation in response to therapy and in silico prognostic evaluation of EGFR-MAPK in HNSCC - Rong, Chao; Muller, Marie France; Xiang, Fang; Jensen, Alexandra; Weichert, Wilko; Major, Gerald; Plinkert, Peter K.; Heß, Jochen; Affolter, Annette (British journal of cancer, 2020)
Head and neck squamous cell carcinoma (HNSCC) patients frequently develop treatment resistance to cetuximab, a monoclonal antibody against EGFR, as well as radiotherapy. Here we addressed extracellular signal-regulated kinase 1/2 (ERK1/2) regulation by cetuximab or fractionated irradiation (IR) and conducted in silico prognostic evaluation of the EGFR-MAPK axis in HNSCC.
Gesehen am 25.11.2021